A Review Paper on Skills Mismatch in Developed and Developing Countries - Senkrua, Akkaya (International Journal of Sustainable Development & World Policy, 2021)
The focus of this review research is on skill mismatch rather than educational mismatch. Specifically, this research examines the definition, extent, measurement of skill mismatch, and the impact of skill mismatch on earnings, productivity, and job satisfaction of employed individuals. Skill mismatch occurs when a worker’s possessed skills are incompatible with the required task-related skills. Skill underutilization or overskilling arises when the skills of an employed individual exceed those required to perform the job. On the other hand, skill overutilization or underskilling ensues when a worker’s skills are below those required to perform the task. The extent of skill mismatch varies from country to country and by measurement approaches: subjective (self-assessment) and objective approaches. The literature review also reveals that underskilling often results in a wage premium and overskilling in a wage penalty. In addition, skill mismatch has a negative impact on productivity and job satisfaction.